Pengaruh Kepuasan, Motivasi Dan Beban Kerja Terhadap Kinerja Karyawan PT Aurora Nova Tech Batam - Anugrah, Fernando; Wasiman, Wasiman (FAKULTAS EKONOMI DAN BISNIS UNIKARTA, 2024)
The purpose of this study is to define the influence of satisfaction, motivation and workload on employee performance at PT Aurora Nova Tech Batam. In this study is using quantitative research approach with the nature of replication research. This study have population of 104 peoples and using a non-probability sampling technique where the sample size was the same as the population, namely 104 people. This research obtained the results show (1)Satisfaction has a significant and positive effect on the performance of PT Aurora Nova Tech employees. (2)Motivation has a significant and positive effect on the performance of PT Aurora Nova Tech employees. (3)Workload has a significant and positive effect on the performance of PT Aurora Nova Tech employees. (4)Satisfaction, motivation and workload simultaneously have a significant and positive effect on the performance of PT Aurora Nova Tech Batam employees. The results of this research shows that satisfaction, motivation and workload simultaneously influence employee performance at PT Aurora Nova Tech with a coefficient of determination of 43.5%.